A Connection Admission Control Based on Real Time Traffic Statistics DOI: 10.14209/jcis.1995.5 - Motoyama, S.; W. Petr, D.; S. Frost, V. (Journal of Communication and Information Systems, 2015)
A connection admission control based on real time traffic statistics is presented in this paper. The method consists of estimating the distribution of the aggregate sources based on the histogram of the number of cells arriving in a fixed interval τ and it is used in conjunction with the new call distribution estimated off-line by measurement or simulation. The new distribution of aggregate sources is obtained using the convolution technique and before the acceptance of a new call. The cell loss ratio (CLR) is evaluated by using this new distribution and it is examined if CLR satisfies required quality of service (QoS). The feasibility and effectiveness of the method are demonstrated by simulation.